Strengthening of RC members using post-tensioned metal straps: state of the research - T. Imjai; U. Chaisakulkiet; R. Garcia; K. Pilakoutas (International Association of Lowland Technology, 2018)
This article reviews the state of the research on a novel and cost-effective strengthening technique for substandard reinforced concrete (RC) structures that uses Post-Tensioned Metal Straps (PTMS). The technique applies active confinement around RC structures by post-tensioning metal straps using steel strapping tools as those used in the packaging industry. The literature survey in this study indicates that some research has been carried out in strengthening normal and high-strength concrete cylinders, columns, lap-spliced elements, beams in flexure, beams and joints in shear, as well as full-scale structures tested on a shake table. Analysis and design models also exist, thus indicating that the technique is reaching maturity. Overall, the experimental results available in the literature indicate that the use of PTMS strengthening is very successful at enhancing the capacity and ductility of structures. Consequently, the PTMS provide a fast and cost-effective strengthening solution in comparison to the other traditional strengthening methods. This study contributes towards a better understanding of the potential use of the PTMS technique as strengthening/retrofit solution, as well as towards highlighting future research needs. Ongoing research work on PTMS at Rajamangala University of Technology Tawan-Ok is also summarised and commented upon.